Comparison of robust Capon beamforming based on weighted sparse constraints - LIN Zhen (Journal of Shanghai Normal University (Natural Sciences), 2020)
The performance of several Capon adaptive beamforming algorithms which used the weighted sparse constraints were analyzed and compared.These algorithms using the sparse distribution characteristics of the antenna array gain would suppress side lobes,reduce interference nulling and improve the system robustness.The simulation results demonstrated that the sparsity constraint Capon beamforming (SCCB)algorithm and the weight sparsity constraint Capon beamforming(WSCCB) algorithm embodied lower side lobes and interference nulling than the traditional Capon beamforming algorithm.However,there still existed inaccurate interference nulling phenomenon.